ANALISIS PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - Jonnadi, Arius; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT Economic growth and poverty is an important indicator to see the success of a country's development. This study aims to determine and analyze the two-way influence between economic growth and poverty in Indonesia: (1) The effect of unemployment, poverty, investments and economic growth. (2) The effect of investment, life expectancy, literacy, and length of education, and economic growth on poverty.This study uses panel data or pooled time-series crossection using time series data from the years 2005-2009, and the crossection is that there are 33 provinces in Indonesia. The method used is descriptive and econometric analysis using a model of simultaneous equations (simultaneous equations models) with two-stage least squares method (Two-Stage Least Square 2SLS) using Indirect Least Square (ILS). The results showed that there is a two-way interplay between economic growth and poverty. Significant effect on economic growth in poverty reduction, especially in rural areas there are many pockets of poverty. the opposite of poverty is also a significant effect on economic growth. Through improved access to capital, quality of education (literacy and increased length of education) and health (increased life expectancy) of the poor can increase their productivity in the attempt during the period 2000-2009. The unemployment rate, and significant investment on economic growth. Furthermore, investments in domestic and foreign investments, life expectancy, literacy and school longer a significant effect on the number of poor. Based on these findings the policy the government should do is spur economic growth through the expansion of investment especially in agriculture (agribusiness and agro-industries) in rural areas where many poor people depend. Recommended to the government in order to spur economic growth in urban areas in order to prioritize employment in which informal sector in general the poor do business. Whereas in rural areas run projects that are capital - intensive investment to open up employment opportunities, especially in the agricultural sector. Furthermore, it also advised the government both at central and regional levels through the state budget and regional budgets in order to further enhance the percentage of budget allocation on health and education to improve the quality of human resources of Indonesia's population. In order to improve the quality of human resources in Indonesia suggested that the government should also continue to run the program compulsory 9 (nine) years, and scholarships for children from poor families to achieve to improve the quality of their children. Keyword: Economic growth, poverty, unemployment, and investments